INDICATION OF GOLD AND SILVER OCCURRENCE AT SAMPIT BAY, KOTA WARINGIN TIMUR DISTRICT, CENTRAL KALIMANTAN PROVINCE - I Wayan Lugra; Udaya Kamiludin (Marine Geological Institute of Indonesia, 2013)
The study area is fluviatile deposit which consists of yellow to light gray loose sand, iron oxide, and kaoline spreading from the land shallowing to sea direction. Concentration grade for determining of gold and silver content used a total analysis of the hot mixture HF-HNO3-HClO4 with measurements